2014
DOI: 10.18686/esta.v1i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Study on Development and Application of Microwave Technology

Abstract: <p>Microwave technology in just a few decades has penetrated into all walks of life, to social development and people's life had a profound impact. On the basis of the development of the microwave, the details of the mechanism of microwave heating and microwave sterilization of both technologies, and microwave heating conditions and characteristics of clarification, in addition, also includes microwave technology is widely used in various fields, while microwave technology for the existing problems are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Modeling of infiltration of liquids in porous media is a well-studied subject, especially in the field of hydrology where it is used to model seepage of water through porous soils and rocks. 29,30 The physics of resin flow into a mold under pressure is similar to the seepage problem and so similar approaches have been used also to model the flow of resin into a mold containing fiber mats. 23,[31][32][33][34][35][36][37][38] The models are used in these cases to determine the resin flow front and mold filling times corresponding to different infiltration conditions.…”
Section: Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Modeling of infiltration of liquids in porous media is a well-studied subject, especially in the field of hydrology where it is used to model seepage of water through porous soils and rocks. 29,30 The physics of resin flow into a mold under pressure is similar to the seepage problem and so similar approaches have been used also to model the flow of resin into a mold containing fiber mats. 23,[31][32][33][34][35][36][37][38] The models are used in these cases to determine the resin flow front and mold filling times corresponding to different infiltration conditions.…”
Section: Characterizationmentioning
confidence: 99%
“…Studies o derived SiC ceramic 25 and SiC/SiC c shown that porosity decreases and mecha prove with the increasing number of PIP show that increasing pyrolysis temperatu tration of SiC fillers in polycarbosilane improved mechanical properties in two-d SiC (C/SiC) composites fabricated using Starting with pyrolysis of a "cured prepreg-based composite, each processin process involves infiltration of a precera porous ceramic preform followed by a py which the polymer is converted into ceram cess modeling is focused on these two ste Modeling of infiltration of liquids in well-studied subject, especially in the where it is used to model seepage of wa soils and rocks. 29,30 The physics of resin under pressure is similar to the seepage pr lar approaches have been used also to mod into a mold containing fiber mats. 23,[31][32][33][34][35][36][37][38] T in these cases to determine the resin flow ing times corresponding to different infilt Preceramic polycarbosilane polymers as precursors to make ceramic fibers 10,3 trix.…”
mentioning
confidence: 99%
See 1 more Smart Citation